Moving Meditation : The Alexander Technique for Performing Arts Students...and the Rest of Us! - Melamed, Ellen (Cognella Academic Publishing, 2019)
Moving Meditation: The Alexander Technique for Performing Arts Students...and the Rest of Us! explores the intersection of creativity and the mind-body relationship through the Alexander Technique, an educational method by which individuals can increase creative thinking, live with greater levels of consciousness, and decrease physical pain and tension. The book begins with a chapter about creativity, habitual behavior, and transformation.